2014
DOI: 10.1002/ijc.29346
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of altered expression and activity levels of CK1δ and ɛ on tumor growth and survival of colorectal cancer patients

Abstract: Colorectal cancer (CRC) is the fourth leading cause of cancer related death worldwide due to high apoptotic resistance and metastatic potential. Because mutations as well as deregulation of CK1 isoforms contribute to tumor development and tumor progression, CK1 has become an interesting drug target. In this study we show that CK1 isoforms are differently expressed in colon tumor cell lines and that growth of these cell lines can be inhibited by CK1-specific inhibitors. Furthermore, expression of CK1d and E is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 39 publications
(96 reference statements)
5
27
0
Order By: Relevance
“…Other cis-eQTL effects for CSNK1D variants include rs9901910 for DCXR (dicarbonyl/L-xylulose reductase) and rs7503429 for SLC16A3 , DCXR and STRA13. Although several variants in our study were predicted to have direct functional effects on expression of the aforementioned genes, it has been reported that mutations in CSNK1D, encoding for a serine-threonine protein component of the beta-catenin destruction complex, can promote the development of CRC (37). CSNK1D is located close to SLC16A3 , encoding a monocarboxylate transporter, with potential for overlapping regulatory elements.…”
Section: Discussionmentioning
confidence: 83%
“…Other cis-eQTL effects for CSNK1D variants include rs9901910 for DCXR (dicarbonyl/L-xylulose reductase) and rs7503429 for SLC16A3 , DCXR and STRA13. Although several variants in our study were predicted to have direct functional effects on expression of the aforementioned genes, it has been reported that mutations in CSNK1D, encoding for a serine-threonine protein component of the beta-catenin destruction complex, can promote the development of CRC (37). CSNK1D is located close to SLC16A3 , encoding a monocarboxylate transporter, with potential for overlapping regulatory elements.…”
Section: Discussionmentioning
confidence: 83%
“…As already described in previous studies, mutations in the coding sequence for CK1δ cannot only influence the activity of the enzyme but also the binding and efficacy of small molecule inhibitors [2,21]. Therefore, the sensitivity of CK1δ hyperactive mutants toward different CK1-specific inhibitors was analyzed and residual kinase activities upon inhibitor treatment are summarized in Table 2.…”
Section: Hyperactive Ck1δ Mutants Are More Sensitive To Different Ck1mentioning
confidence: 99%
“…Dysregulation of CK1δ expression and/or activity has been observed in different types of disorders, including cancer. So far, different CK1δ mutations have been already identified and seem to have a higher oncogenic potential in comparison to CK1δ wild type [1,2]. Recently, the CK1δ T67S mutant has been identified in colon and rectal cancer (CRC) and this mutant showed increased in vitro kinetics and is associated with increased cell proliferation and tumor growth in both cell culture and in a subcutaneous tumor xenotransplantation mouse model [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other studies reported that a significant number of patients with a high level of CK1ε expression are the ones that have better prognosis and survival [8,22,30]. Nevertheless, this source of contradiction must be properly interpreted.…”
Section: Therapeutic Relevancementioning
confidence: 92%